1 3/10·b=39
(1·10+3)·b/10=39
13b/10=39
13b=39·10
13b=390|:13
<u>b=30</u>
<em>Answer: 30</em>
The function of f(x)=-x+4x-3 is 3x-3. I hope this helps. :)
Answer:
x = 1 ±√89
Step-by-step explanation:
We have the equation:
(x+7)(x-9) = 25
Using distributive property:
x(x-9) + 7(x-9) = 25
x²- 9x + 7x - 63 -25 = 0
x²- 2x - 88 = 0
To complete squares we need to add and subtract 1, as follows:
x²- 2x - 88 +1 -1 = 0
x²- 2x +1 -88 -1 = 0 (this is a perfect square)
(x - 1)² - 89 = 0
Solving for x:
(x - 1)² = 89
x - 1 = ±√89
x = 1 ±√89
Use Pythagorean theorem:
9i-j = sqrt (9^2 - 1^2) = sqrt(81-1) = sqrt80
now divide both terms in V by that:
u = 9/sqrt(80)i - 1/sqrt(80)j
see attached picture: